Conflicts, Dilemma and Outlets: Chinese Administrative Rule of Law under the Conditions of the Information Age - 邓晔; 宋莉娜 (가천법학, 12(1), 2019)
With the coming of the information era, Chinese administrative rule of law is experiencing an profound reform not only in the field of administrative basic theory, but in the field of administrative practice, not only in the field of administrative execution, but in the field of administrative legislation, not only in the field of real world but in the field of virtual world. Confronting such a reform, scholars of Chinese administrative law should scheme ahead to reflect upon the present theory of administrative law from all-round aspects, timely adjust related theory so as to the construction of administrative rule of law. This article mainly analyses the conflicts, dilemma of Chinese administrative rule of law, points out some outlets of Chinese administrative rule of law under the conditions of the information age. KCI Citation Count: 0